Student participation in the 2019 general election activities to realize the practice of Pancasila - Suyoko; Abdul Haris Subarjo (Trigin Publisher, 2023)
The 2019 election for President, Vice President and members of the legislature has been held and has ended. The implementation of the 2019 General Election attracted many parties to evaluate it. Students as the next generation of the Nation are expected to participate in General Election activities, especially Adisutjipto Dirgantara College of Technology Students who are a part of students in general. In the 2019 General Election activities, out of 100 respondents, 87% took part in General Election activities as voters. The involvement of these students is also the general election committee, student participation is divided into committee parts, including: being the general election organizing committee, and witnessing the general election process at TPS. Based on the interviews, 12 percent of the data was obtained from participating in committee activities and witnesses. From the 12 percent data obtained details of 9 percent as general election committee, 3 percent as witnesses. If we look at the data, it can be seen that students as the younger generation also contribute to the success and expedite the general election process.